2019
DOI: 10.1128/aac.02669-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Chlorhexidine Compared with Seven Antifungal Agents against 98 Fusarium Isolates Recovered from Fungal Keratitis Patients

Abstract: Fungal keratitis is a common but severe eye infection in tropical and subtropical areas of the world. In regions with a temperate climate, the frequency of infection is rising in patients with contact lenses and following trauma. Early and adequate therapy is important to prevent disease progression and loss of vision. The management of Fusarium keratitis is complex, and the optimal treatment is not well defined. We investigated the in vitro activity of chlorhexidine and seven antifungal agents against a well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
4
16
0
3
Order By: Relevance
“…Our susceptibility data suggest that the standard chlorhexidine concentration used for the treatment of Acanthamoeba keratitis (0.02%) may also be effective for the treatment of fungal keratitis. This is also supported by published in vitro data [ 16 , 17 , 18 ]. The main difficulties with topical antifungal treatment of ocular infections are poor ocular penetration and local bioavailability, the limited number of preparations, and drug toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…Our susceptibility data suggest that the standard chlorhexidine concentration used for the treatment of Acanthamoeba keratitis (0.02%) may also be effective for the treatment of fungal keratitis. This is also supported by published in vitro data [ 16 , 17 , 18 ]. The main difficulties with topical antifungal treatment of ocular infections are poor ocular penetration and local bioavailability, the limited number of preparations, and drug toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…There is increasing evidence that chlorhexidine may be effective for the treatment of Fusarium keratitis, supported by both clinical trials and in vitro studies (Rahman et al, 1997(Rahman et al, , 1998. We recently showed that chlorhexidine exhibited fungicidal activity against a broad range of filamentous fungi including Fusarium species, at concentrations that could be readily achieved clinically (Oliveira dos Santos et al, 2019). The activity of chlorhexidine against Acanthamoeba and bacteria makes it a very attractive agent for local treatment of keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Rational treatment choices are also hampered by the lack of correlation between MIC and drug efficacy. The most frequently isolated Fusarium species complexes (FSSC, FOSC and FFSC) are generally multidrug resistant in vitro and any activity is at best fungistatic (Oliveira dos Santos et al, 2019). The use of MICs to guide treatment choices is limited due to the fact that through topical therapy the fungus is exposed to very high drug concentrations and thus may respond despite a high in vitro MIC.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies showing that CHL exhibits in vitro antifungal activity against Fusarium spp. Oliveira et al found that CHL exhibited fungicidal activity against 90% of tested F. oxysporum strains and 100% of tested F. solani strains when evaluating 98 strains isolated from fungal keratitis patients [ 11 ]. Xu et al found that the MIC range for CHL is 8–32 μg/mL, while the MIC 90 value of chlorhexidine was 32 μg/mL for 24 F. solani strains [ 12 ].…”
Section: Discussionmentioning
confidence: 99%